Analisa Pemilihan Air Mineral dan Rekomendasi Terbaik dengan Metode SMART (Simple Multy Atribute Rating Technique) - Leman, Dedi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Everyone needs drinking water which is increasing in line with the increasing population of Indonesia, but while the amount and level of drinking water decreases so people are looking for other options to get healthy drinking water and good levels. major developments in the sale of bottled drinking water, along with the arrival of many bottled drinking water products that are spread throughout the country bring increasingly intense competition among bottled beverage vendors. Various kinds of prices have a good and advanced impact on purchasing decisions. With the simple multy attribute rating technique, the method will find out the best mineral water according to the selected criteria. The purpose of this study is to examine the good levels of products, prices and the introduction of purchasing drinking water into a decision in purchasing bottled water. This research results that various kinds of product quality have a positive and significant influence on people's purchasing decisions in buying bottled water